Pengaruh Persepsi Legitimasi Polisi Terhadap Kepatuhan Hukum Lalu Lintas pada Generasi Z di Kota Aceh Tenggara Perspektif Teori Konstruktivisme Sosial: Penelitian - Indah Fitria; Agusmidah; Rosmalinda (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Compliance with traffic laws is a key indicator in ensuring order and safety on the roads. Traffic violations continue to occur in various regions, including Aceh Tenggara, particularly among Generation Z. This generation is characterized as dynamic, critical of authority, and highly influenced by social media in shaping their perceptions and behaviors. This phenomenon indicates that repressive law enforcement approaches are no longer fully effective without the support of social legitimacy toward authorities and law enforcement actions. This study aims to analyze the influence of perceived police legitimacy on traffic law compliance among Generation Z. Police legitimacy is understood as the public’s trust in the authority of law enforcement officers to uphold the law fairly, with integrity, and transparently. This research employs a qualitative approach grounded in the social constructivism paradigm of Peter Berger and Thomas Luckmann to understand how social reality is constructed through interactions between individuals and authoritative institutions. The findings show that perceptions of police legitimacy significantly influence compliance levels. Thus, the study affirms that social legitimacy cannot be built solely through formal authority and sanctions, but also through humanistic communication, equitable services, and the presence of officers who embody moral exemplarity within society.